Fashion chronicles of María Luz Morales: quality jornalism: Diario de Barcelona (1948-1953) - Arroyo Cabello, María (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
María Luz Morales, one of the first university-trained journalists, forerunner of cultural journalism, director of El Hogar y la Moda and La Vanguardia, chronicler of El Sol and Diario de Barcelona, cultivated all genres, especially the chronicle of fashion, theater and film criticism. The objetive is to verify the journalistic quality of his fashion chronicles in the Dia-rio de Barcelona during the postwar period. The methodology is based on content analysis using the VAP (Journalistic Added Value) method as a reference. The results indicate that the 121 chronicles meet the established quality indices: topicality, presence of the journalist, professional sources; specific language, ad-jectives, photos, illustrations; continuity of the theme and signature, background, explanation and argued critique.